OXYGEN-ISOTOPE DISTRIBUTION IN DARK INCLUSIONS IN CARBONACEOUS CHONDRITES - Ustinov V.I.; Ul'yanov A.A.; Ivanov A.V.; Shukolyukov Y.A.; Gavrilov Y.Y. (My University, 1987)
The paper reports on a study of the so-called dark inclusions in carbonaceous chondrites in order to accumulate experimental data on meteorite components, the scale of oxygen-isotope fractionation in cosmic processes, and the patterns of oxygen-isotope distribution in meteorite material, formed in different stages of evolution of the solar nebula. The work was done on two dark inclusions from the Yefremovka chondrite (Ye-39 and Ye-53), on one inclusion from the Allende chondrite (Al) and on carbonaceous xenoliths from the Kaidun chondrite. Being fine grained, this material could not eaisly be mineralogically identified. Study materials, methods and results are discussed.